2021
DOI: 10.3389/fonc.2021.608191
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Artificial Intelligence Based on Routine Laboratory Results for the Early Diagnosis of Multiple Myeloma

Abstract: ObjectiveIn order to enhance the detection rate of multiple myeloma and execute an early and more precise disease management, an artificial intelligence assistant diagnosis system is developed.Methods4,187 routine blood and biochemical examination records were collected from Shengjing Hospital affiliated to China Medical University from January 2010 to January 2020, which include 1,741 records of multiple myeloma (MM) and 2,446 records of non-myeloma (infectious diseases, rheumatic immune system diseases, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In their study, MM and non‐myeloma were mixed and randomly divided into training and test subsets. The best model in their study yielded a better performance (PPV = 92.9%, sensitivity = 90%, F‐measure = 91.50%, AUC = 97.50%) compared with ours (PPV = 88.50%, sensitivity = 85.20%, F‐measure = 86.80%, and AUC = 96.80%) 19 . However, the data in the prior study were derived from only a single healthcare institution, and immunoglobulin (A, G, and M) levels were also utilized as input features.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In their study, MM and non‐myeloma were mixed and randomly divided into training and test subsets. The best model in their study yielded a better performance (PPV = 92.9%, sensitivity = 90%, F‐measure = 91.50%, AUC = 97.50%) compared with ours (PPV = 88.50%, sensitivity = 85.20%, F‐measure = 86.80%, and AUC = 96.80%) 19 . However, the data in the prior study were derived from only a single healthcare institution, and immunoglobulin (A, G, and M) levels were also utilized as input features.…”
Section: Discussionmentioning
confidence: 58%
“…To our knowledge, to date, there has been only one published study that addresses the diagnosis of MM by combining ML and serum biomarkers 19 . In their study, MM and non‐myeloma were mixed and randomly divided into training and test subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning is a part of AI and is related to the ability to learn from large amounts of data (a set of lessons) [65]. Recently, Yan et al [66] demonstrated that Cancer cachexia is a disorder characterized by wasting of muscle and adipose tissue, but changes in white adipose tissue (WAT) phenotype, i.e., the conversion of the white adipocytes in "beige" cells, was only described recently [57,58]. Interestingly, both high adipose tissue radiodensity and increased adipose tissue glucose uptake may be related to this phenomenon, and therefore, they may be early markers of cancer cachexia.…”
Section: Artificial Intelligence For Estimating Total Metabolic Tumor Volume In Multiple Myelomamentioning
confidence: 99%
“…Machine learning is a part of AI and is related to the ability to learn from large amounts of data (a set of lessons) [65]. Recently, Yan et al [66] demonstrated that machine learning models derived from routine laboratory results can accurately diagnose MM and can increase the rate of early diagnosis.…”
Section: Artificial Intelligence For Estimating Total Metabolic Tumor Volume In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation